Des études en quête d’auteurs : instructions et questionnaires sur l’habitat traditionnel en France, fin XIXe-milieu XXe siècle - Pascal Riviale (In Situ)
Because of an incessant growing urbanization and an evolution in the economic and social structures, the French architectural landscape has radically transformed itself since the 19th century. Facing the threats of losing what was considered – more or less early - as being an integral element of the national cultural heritage, some scientific and museum institutions initiated from the end of the 19th century surveys and studies of the different types of traditional architecture existing on the territory. The archives of the former Popular Arts and Traditions National Museum (now stored at the National Archives) allow documenting some survey campaigns and highlighting the important contribution of the informants requested on the spot (correspondents, local scholars, ‘institutionals’, etc) to support this patient documentary work. Two examples will be highlighted (the first one in 1889, the second one in the 1940s), and will address the issue of the typology of these “pioneer actors” of the patrimony.